Factors Affecting The Compatibility Between Education Outcomes And The Labor Market - صيوح لؤي; ميا علي; الرفاعي عبد الهادي; العشعوش أيمن; غدير باسم; إسماعيل عصام; حيدر عز الدين; إسماعيل رولا; خليل فادي; ناعسة عبير; عيسى جميل; صالح غسان; et al. (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Increased interest in human capital as one of the driving forces of economic development, and with it increased interest in studying how to bridge the gap between higher education outputs and labor market inputs. Hence the importance of research in analyzing the problem of incompatibility between the outputs of higher education and the needs of the labor market in Syria. The problem of incompatibility between the outputs of higher education at “Tishreen University” (the research sample) and the needs of the labor market was analyzed to identify the requirements of the labor market and analyze the factors that govern The relationship between job offer and demand in order to provide a mechanism that enables reconciling between the available university majors and the requirements of the labor market in terms of the quality of university majors, the skills acquired by the graduate and their compatibility with the requirements of the labor market. Two questionnaires were designed for the purpose of data collection, the first to measure the opinion of employers in both parts (public and private) and the second to measure the opinion of university graduates. The study reached a set of results, the most important of which are: University graduates have a good ability to commit to work and its requirements and learn the skills it needs, and suffer from poor qualification in terms of practical skills complementing their academic degrees required by the labor market, due to poor coordination between educational institutions and labor market organizations. The public sector focuses greatly on securing job opportunities for various segments of society, and tends to employ more numbers than its needs, unlike the private sector, which works to employ a specific number according to its needs without increasing or decreasing. The research team recommended the need to focus on the practical side to achieve integration with the theoretical side in education (university and technical) and to develop training units for each college and technical institute. Introducing universities as houses of expertise and advice, especially with regard to the localization of projects of an economic nature. And reconsidering investments employing manpower in the coast, especially after the demographic change that occurred due to the war on Syria through: Encouraging the establishment of (small projects - integrated production projects (agricultural - industrial) that generate job opportunities, especially for graduates